2015
DOI: 10.1103/physrevd.91.064059
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical mass ejection from binary neutron star mergers: Radiation-hydrodynamics study in general relativity

Abstract: We perform radiation-hydrodynamics simulations of binary neutron star mergers in numerical relativity on the Japanese "K" supercomputer, taking into account neutrino cooling and heating by an updated leakage-plus-transfer scheme for the first time. Neutron stars are modeled by three modern finite-temperature equations of state (EOS) developed by Hempel and his collaborators. We find that the properties of the dynamical ejecta of the merger such as total mass, average electron fraction, and thermal energy depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
399
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 312 publications
(444 citation statements)
references
References 58 publications
33
399
11
1
Order By: Relevance
“…Importantly, we found that these features do not depend sensitively on the astrophysical conditions for the majority of the ejecta (but see Ref. [16][17][18] for a possible increase of the initial electron fraction which may have an impact on the abundance patterns). We have also shown that these features do not depend in general on the nuclear mass model used.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Importantly, we found that these features do not depend sensitively on the astrophysical conditions for the majority of the ejecta (but see Ref. [16][17][18] for a possible increase of the initial electron fraction which may have an impact on the abundance patterns). We have also shown that these features do not depend in general on the nuclear mass model used.…”
Section: Discussionmentioning
confidence: 93%
“…We note that such a robust scenario is quite attractive as it might arXiv:1409.6135v2 [astro-ph.HE] 1 Oct 2015 explain the occurrence of r-process elements above the second peak in solar proportion as observed in very old metal-poor stars [15]. Recent simulations suggest that the electron fraction of part of the ejecta may be raised by neutrino processes [16][17][18]. However, the sensitivity of these results to the treatment of neutrino radiation transport in NS mergers simulations remains to be explored.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations